Parents matter: Parent acceptance of school‐based executive functions interventions relates to improved child outcomes. Issue 7 (8th January 2022) - Rothschild, Leah B.; Ratto, Allison B.; Kenworthy, Lauren; Hardy, Kristina K.; Verbalis, Alyssa; Pugliese, Cara; Strang, John F.; Safer‐Lichtenstein, Jonathan; Anthony, Bruno J.; Anthony, Laura G.; Guter, Madison M.; Haaga, David A. F.
Abstract: Objectives: School‐based interventions with parent‐training components might improve access among lower‐income families to effective help for children with neurodevelopmental disorders. This potential might be realized, however, only if parents perceive the interventions as acceptable and therefore engage with treatment. Methods: Parents ( N  = 124) of 3rd−5th grade students diagnosed with Autism Spectrum Disorder or Attention‐Deficit/Hyperactivity Disorder rated the acceptability of their child's treatment (one of two culturally responsive behavioral interventions). Parent engagement was measured through attendance at parent training sessions and the extent to which they read a corresponding workbook. Results: Education and income correlated inversely with parent perceptions of treatment acceptability. Acceptability correlated positively with engagement, more strongly among lower‐income families. Acceptability had an indirect effect on treatment outcome, mediated by parent engagement. Conclusions: Treatment providers should focus on strategies to increase parent acceptability, with particular attention to improving access for lower‐income families.